Genome-wide association study to identify genetic determinants of severe asthma. Issue 9 (5th May 2012) - Wan, Y I; Shrine, N R G; Soler Artigas, M; Wain, L V; Blakey, J D; Moffatt, M F; Bush, A; Chung, K F; Cookson, W O C M; Strachan, D P; Heaney, L; Al-Momani, B A H; et al.
Abstract : Background: The genetic basis for developing asthma has been extensively studied. However, association studies to date have mostly focused on mild to moderate disease and genetic risk factors for severe asthma remain unclear. Objective: To identify common genetic variants affecting susceptibility to severe asthma. Methods: A genome-wide association study was undertaken in 933 European ancestry individuals with severe asthma based on Global Initiative for Asthma (GINA) criteria 3 or above and 3346 clean controls. After standard quality control measures, the association of 480 889 genotyped single nucleotide polymorphisms (SNPs) was tested. To improve the resolution of the association signals identified, non-genotyped SNPs were imputed in these regions using a dense reference panel of SNP genotypes from the 1000 Genomes Project. Then replication of SNPs of interest was undertaken in a further 231 cases and 1345 controls and a meta-analysis was performed to combine the results across studies. Results: An association was confirmed in subjects with severe asthma of loci previously identified for association with mild to moderate asthma. The strongest evidence was seen for the ORMDL3 / GSDMB locus on chromosome 17q12-21 (rs4794820, p=1.03×10 (−8) following meta-analysis) meeting genome-wide significance. Strong evidence was also found for the IL1RL1 / IL18R1 locus on 2q12 (rs9807989, p=5.59×10 (−8) following meta-analysis) just below this threshold. No novel loci for susceptibility to severe asthma met strict criteria for genome-wide significance. Conclusions: The largest genome-wide association study of severe asthma to date was carried out and strong evidence found for the association of two previously identified asthma susceptibility loci in patients with severe disease. A number of novel regions with suggestive evidence were also identified warranting further study.